Effect of hydroseeding media materials on soil stability from landslide sites - Zairina, Anisa; Soemarno, Soemarno; Rachmansyah, Arief; Yanuwiadi, Bagyo; Leksono, Amin Setyo (Brawijaya University, 2025)
Landslides can cause soil and land quality degradation. Soil originating from landslide sites has less stable aggregates because it is nutrient-poor. This study aimed to evaluate the effect of hydroseeding media materials on soil stability after landslides. This study was conducted in two landslide areas in Pujon District, Malang Regency (112.417958 E, 7.867472 S) and toll road KM 78 Purwodadi, Pasuruhan Regency (112.726777 E, 7.804978 S), East Java. Soil analysis was carried out with parameters including soil physical characteristics data (bulk density, specific gravity, water content, porosity, texture and permeability) and soil chemical characteristics (organic matter, organic C, N, P, K, pH, CEC, exchangeable K, Na, Ca, Mg, total N and C/N ratio). The application of hydroseeding media was carried out with a combination of the following media: mulch (M), blotong (B), and fertilizer (cow manure; F). The results showed that the two-material formula generally had soil aggregates that were more resistant to water droplets. Soil aggregates with the MB formula treatment had the best aggregate stability compared to ten hydroseeding formulas with other material combinations.